Monocrystalline hematite nanostructures: three-dimensionally oriented aggregation synthesis and their comparative visible-light photocatalytic activities. Issue 14 (20th March 2017) - Li, Pengwei; Yan, Xiaole; Ji, Jianlong; Wu, Yiduo; Hu, Jie; Wang, Ying; Jiang, Huabei; Zhang, Wendong
Abstract : Intelligent three-dimensionally oriented aggregation of nanobuilding blocks during the formation of α-Fe2 O3 single crystals with a nano-saucer structure has been studied. Abstract : Intelligent three-dimensionally oriented aggregation of nanobuilding blocks during the formation of α-Fe2 O3 single crystals with a nano-saucer structure has been studied. The hematite truncated hexagonal bipyramids assembled together with the aid of dihydrogen phosphate ions and grew along the <120> direction to form a slice structure, then the slices piled up layer by layer along the [006] zone axis to form the brand-new geometry of saucer-like nanoparticles. On the basis of the small size, rough surface and loose, zigzag edge characteristics of the 3D assembly structure, the novel saucer nanoparticles exhibited distinguishable absorption and specific surface area (SSA) properties, thus serving as the possible origin of their comparative visible-light photocatalytic activities on the degradation of cationic dye rhodamine B. These characteristics make them promising candidates for catalysts and sensing materials.